Effectiveness of World Bank Support for Community-Based and -Driven Development : an OED Evaluation. - Kumar, Nalini (Online access: World Bank World Bank Open Knowledge Repository., 2005)
Participatory approaches that involve local communities in their own development have gained substantial support among international donors over the past quarter-century and have become increasingly important in the work of the World Bank. Community participation is an approach to development that can be used with any Bank lending instrument and across sectors. Projects can involve communities in different ways-by sharing information, consulting, collaborating, or empowering them. The process of involving communities in project activities is also expected to contribute in most cases to communi.